ALPHA-GAL SYNDROME: AN EMERGING TICK-INDUCED ALLERGY TO MAMMALIAN MEAT – CURRENT KNOWLEDGE AND CLINICAL IMPLICATIONS - Iga Kałka; Julia Szmuc; Natalia Kaczmarczyk; Jakub Robert Skalski; Karolina Halat; Antoni Hajdas; Gabriela Daniel; Łukasz Ćmok; Justyna Chudy; Julia Dobrowolska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Alpha-gal syndrome (AGS) is an emerging IgE-mediated allergy to galactose-α-1,3-galactose (α-gal), a carbohydrate epitope present in most non-primate mammals. The condition is typically triggered by tick bites and is characterized by delayed hypersensitivity reactions occurring several hours after ingestion of mammalian meat or exposure to products containing α-gal. Increasing tick populations and environmental changes have contributed to the growing recognition of this condition worldwide.Aim: This review aims to summarize current knowledge on the epidemiology, immunopathogenesis, clinical manifestations, diagnosis, and management of alpha-gal syndrome, with particular emphasis on its clinical implications and challenges in everyday medical practice.Materials and methods: A narrative review of the literature was conducted using publications indexed in PubMed. Clinical studies, case series, mechanistic studies, and review articles published between 2009 and 2026 were included. The evidence was analyzed and synthesized across key thematic areas, including epidemiology, pathophysiology, clinical presentation, diagnostic approaches, and management strategies.Results: AGS represents a unique model of delayed IgE-mediated food allergy. Clinical manifestations range from isolated gastrointestinal symptoms and urticaria to severe anaphylaxis. Diagnosis is primarily based on the detection of serum IgE antibodies to α-gal combined with a compatible clinical history. The cornerstone of management remains avoidance of mammalian-derived foods and prevention of further tick bites. Recent evidence also highlights the potential role of cofactors, biological therapies, and non-dietary exposures in triggering allergic reactions.Conclusions: Alpha-gal syndrome is an increasingly recognized but still underdiagnosed allergic condition that poses significant diagnostic and clinical challenges. Greater awareness among clinicians and further research into the immunological mechanisms and long-term outcomes of the disease are essential to improve diagnosis and patient management.